HEPATIC PORTAL VENOUS GAS - Stavreski, Nacko; Klinche, Shener; Stojovska Jovanovska, Elizabeta; Bundovska Kocev, Smiljana (Journal of Morphological Sciences, 2023)
Hepatic portal venous gas (HPVG), an ominous radiologic sign, in most of the cases is associated with a severe abdominal disease that requires an urgent surgical intervention. In the medical literature, HPVG has been commonly associated with severe or lethal conditions. The diagnosis of HPVG is usually made by plain abdominal radiography, ultrasonography, color Dopler flow imaging or computed tomography (CT) scan. The increased use of CT scan in the inpatient setting allows early and highly sensitive detection and also recognition of an increasing number of benign and non-life threating causes of HPVG. The prognosis is related to the pathology itself and is not influenced by the presence of HPVG. Key words : hepatic portal vein gas; bowel ischemia/necrosis; pneumatosis intestinalis; abdominal computed tomography scan; acute abdomen. https://doi.org/10.55302/JMS2361127s